Analisis Perilaku Membolos Siswa dan Penanganannya - Faturahman, Faturahman; Pandang, Abdullah; Saman, Abdul (Guidance : Jurnal Bimbingan dan Konseling, 2024)
This research aims to determine 1) the description of students' truancy behavior at SMAN 14 Makassar, 2) the factors that students engage in truancy behavior, 3) the impact of truancy behavior, 4) handling truancy behavior. This type of research is case study research with a qualitative approach. The instruments of this research are observation, interviews and documentation. The subjects of this research were 6 students at SMA 14 Makassar who were identified as having low student attendance. Data collection uses interview and observation techniques. The results of the research show that: 1) Students engage in truancy behavior by storing their bags and leaving during lessons, skipping school, skipping lessons on certain days. 2) Factors that students engage in truancy behavior include, students being lazy about attending lessons, problems with parents, invitations from friends and lots of assignments 3) The impact of truant behavior experienced by students includes, Calls to the guidance and counseling room, Calls from parents, Suspension and Missing Subjects. 4) The treatment carried out is group counseling, individual counseling and classical guidance.